Anthropometry of Iranian Guidance School Students with Different Ethnicities: A Comparative Study. (8th October 2015) - Mehrparvar, Amir Houshang; Hafezi, Rahmatollah; Mirmohammadi, Seyyed Jalil; Mostaghaci, Mehrdad; Davari, Mohammad Hossein
Abstract : Objective . We measured some anthropometric dimensions of Iranian guidance school students selected from different ethnicities. Background . Anthropometric dimensions are used for design of equipment, furniture, and clothing. Furniture with inappropriate design not fulfilling the users' anthropometric dimensions may have a negative effect on health. Method . A total of 7400 Iranian guidance school students aged 12–14 years entered the study and their static anthropometric dimensions were measured. Descriptive statistics such as mean, standard deviation, and key percentiles were calculated. All dimensions were compared among different ethnicities and different genders. Results . This study showed significant differences in a set of 22 anthropometric dimensions regarding gender, age, and ethnicity. Conclusion . According to the results of this study, difference between genders and among different ethnicities should be taken into account by designers and manufacturers of guidance school furniture. Application . This study has prepared a data bank of anthropometric dimensions of 12–14-year-old students which can be used as basic information to find appropriate dimensions of school furniture.